Effects of transcranial electrical stimulation techniques on second and foreign language learning enhancement in healthy adults: A systematic review and meta-analysis. (17th September 2021) - Balboa-Bandeira, Yolanda; Zubiaurre-Elorza, Leire; Ibarretxe-Bilbao, Naroa; Ojeda, Natalia; Peña, Javier
Abstract: Background: Transcranial electrical stimulation (tES) techniques have been used to enhance different cognitive domains such as language in healthy adults. While several reviews and meta-analysis have been conducted on the effects of tES on different language skills (picture naming, verbal fluency, word reading), there has been little research conducted to date on the effects of tES on the processes involved in foreign language learning. Objective: A meta-analysis was performed to quantify the effects of tES on foreign language learning processes (non-words, artificial grammar, and foreign languages), focusing on accuracy, response times and 1-week follow-up effects, if reported by the studies. Results: Eleven studies that had sham condition were reviewed. Nine of them were analyzed, including five using within-participant design, and four that employed between-participant design. The final analysis encompassed nine studies with 279 healthy participants. The analysis showed moderate enhancing effects of tES on overall language learning ( g = 0.50, 95 % CI [0.29, 0.71], p = .0001). However, results were not significant on follow up data ( g = 0.54, 95 % CI [-0.12, 1.20], p = .07), and on response times ( g = 0.50, 95 % CI [-0.1, 1.18], p = .10). The effects were significantly moderated by years of education. Conclusions: The results suggest that tES seems to enhance the mechanisms involved in foreign language learning; however, more research is needed to understand the impact scope of these techniques on language learning processes. Highlights: Analysing effects of transcranial electrical stimulation (tES) on second and foreign language learning related processes. Significant effects of tES were observed on overall language learning enhancement (Hedge's g = 0.51). Effects were significantly moderated by years of education.